Potential of Three Tropical Legumes for Rotation of Corn-Based Cropping System in Thailand - Sukum Chotechaungmanirat, (Agriculture and Natural Resources, 2010)
This study was an attempt to search for a means to assimilate tropical legumes into the existing cropping system of corn in order to improve the productivity of the corn crop. The study consisted of three experiments: 1) a study on the growth of three tropical legumes (lablab bean, Lablab purpureus; thornless mimosa, Mimosa invisa and sesbania, Sesbania speciosa); 2) a study on the seed dormancy of the legumes; and 3) a study on the germination behavior of the soil seed bank of a legume (thornless mimosa) in relation to the growing season of corn. The results of the study showed that lablab bean and sesbania were suitable as rotation crops with a corn crop, while thornless mimosa was able to be assimilated into the corn crop in both rotation cropping and intercropping. The results also showed that thornless mimosa had dormant seeds and that a seed bank for this legume could be created in the soil, so there was no need to sow seeds every year, as mimosa would be reseeded from this soil seed bank.